A Design and Development of an Energy Monitoring System for Solar Power Plants and Inverter Output as an Energy Source in Smart Homes - Munawar, Al; Muchtar, Taufik; Akbar , Zainal (JEAT : Journal of Electrical Automation Technology, 2025)
The increasing demand for sustainable energy has encouraged the use of solar power systems (PLTS) in households; however, the lack of adequate monitoring systems hinders direct assessment of performance. This study designs a real-time monitoring system based on electrical parameters to evaluate the performance of solar panels using the Research and Development (R&D) method, including system design, device assembly, and testing. The ESP32 microcontroller is used as the main control unit, with the PZEM-017 sensor for measuring DC power and the PZEM-004T sensor for AC power. Data is displayed through a web application developed with PHP and MySQL. The results show that the system can accurately display voltage, current, power, and energy, with an average error rate of 2.3% for the DC sensor and 0.3% for the AC sensor, and overall accuracy above 95%. Data transmission runs smoothly. The system is proven effective for energy monitoring in smart homes and has the potential to be enhanced with features such as automatic notifications and AI-based data analysis.